1995
DOI: 10.1073/pnas.92.24.11299
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide inhibits the release of norepinephrine and dopamine from the medial basal hypothalamus of the rat.

Abstract: Previous research indicates that norepinephrine and dopamine stimulate release of luteinizing hormohe (LH)-releasing hormone (LHRH), which then reaches the adenohypophysis via the hypophyseal portal vessels to release LH. Norepinephrine exerts its effect via ol-adrenergic receptors, which stimulate the release of nitric oxide (NO) from nitricoxidergic (NOergic) neurons in the medial basal hypothalamus (MBH). The NO activates guanylate cyclase and cyclooxygenase, thereby inducing release of LHRH into the hypoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…The fact that LPS and interferon treatment inhibits basal and stimulated ACTH secretion from AtT-20 cells is consistent with other studies which show that NO inhibits ACTH secretion (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The effect of LPS upon the pituitary is complex: in the whole animal LPS is often reported to stimulate ACTH secretion (87).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The fact that LPS and interferon treatment inhibits basal and stimulated ACTH secretion from AtT-20 cells is consistent with other studies which show that NO inhibits ACTH secretion (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The effect of LPS upon the pituitary is complex: in the whole animal LPS is often reported to stimulate ACTH secretion (87).…”
Section: Discussionsupporting
confidence: 76%
“…Experimental evidence from neuronal cultures and animal models shows that NO can also inhibit specific secretory responses of neurons. For example, some but not all modes of stimulating hormone secretion from the pituitary are enhanced in the presence of NOS inhibitors (27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…Some studies have suggested an interaction between NO and other neurotransmitters such as dopamine (DA) [18,28,37,51], noradrenaline [51], GABA [63], acetylcholine (Ach) [56,62] and 5-HT [11,23,38,66]. In the medial preoptic area, NO has been shown by a microdialysis method to increase 5-HT and DA levels [38].…”
Section: Considerable Relationship Between Nadph-d-positive Neurons Amentioning
confidence: 99%
“…We have already described the ability of NE to stimulate LHRH release and the fact that dopamine also acts as a stimulatory transmitter in the pathway. Therefore, there is an ultra short-loop negative feedback mechanism to terminate the pulsatile release of LHRH since the NO released by NE would diffuse to the noradrenergic terminals and inhibit the release of NE, thereby terminating the pulse of NE, LHRH and finally LH (24).…”
Section: Role Of No In Control Of Lhrh Releasementioning
confidence: 99%